Cold Compresses Reduce the Perception Level of Artery and Vena Insertion in Hemodialistic Patients - Purnamawati, Dewi; Sulaeman, Ridawati; Rusmini,; Mas’adah,; Wijayanti, GA Sri Puja Warnis; Mawaddah, Ely (International Journal of Psychosocial Rehabilitation, 2020)
Hemodialysis patients experience pain during cannulation (insertion of arteries and veins) due to large cannula, therefore an intervention modality that can control pain by cold compresses for 3 minutes in the insertion area. This study aims to examine the effect of cold compresses on the level of pain perception of arterial and venous insertion of hemodialysis patients. This study uses a randomized subjects post-test only control group method. The population in this study were all kidney failure patients undergoing hemodialysis in the Hemodialysis Room of NTB Provincial Hospital from January to November 2017 as many as 412 people. The total sample using the Slovin formula was obtained as many as 80 respondents consisting of 40 intervention groups and 40 control groups. Purposive sampling technique. Inclusion Criteria Cooperative respondents, not restless, no hypotension (arrhythmia), normal body temperature. Respondent's research was conducted with an information concern, the intervention group cold compress temperature of 13.5°C was given for 3 minutes in the insertion area using a rubber ice bag. Data collection of pain sensations by observation with the aid of the VAS scale (Visual Analog Scale)). Pain sensation felt after cold compresses were analyzed using a paired-sample t-test. The result of the study was ρ = 0.00, meaning that there was a significant difference in the perception of pain in the arteries and veins of hemodialysis patients who were given cold compresses and those who did not. Cold compresses in the area of venous insertion and arteries of hemodialysis patients reduce the sensation of pain due to puncture using a cannula, so this action is recommended in the hemodialysis chamber.